2019
DOI: 10.4103/cjp.cjp_22_19
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases in Stroke

Abstract: Stroke is the second leading cause of death and the leading cause of adult disability worldwide. Despite an impressive amount of neuroprotective agents that has been identified in experimental stroke, none of them proved efficient in clinical trials. There is a general consensus that an effective treatment requires the ability to interact with not one, but multiple pathophysiological cascades at different levels that induced by the insult – cocktail therapy. Luckily, recent progress in the field of epigenetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…MiRNAs are described in cell proliferation and differentiation, apoptosis, fat metabolism and hematopoiesis [ 108 ]. LncRNAs are a regulator of vascular function, and their dysregulation contributes to cardiovascular disease [ 109 , 110 ]. Studies have revealed alterations in miRNA levels in arterial hypertension, dyslipidemia, atherosclerosis, and inflammation [ 111 , 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are described in cell proliferation and differentiation, apoptosis, fat metabolism and hematopoiesis [ 108 ]. LncRNAs are a regulator of vascular function, and their dysregulation contributes to cardiovascular disease [ 109 , 110 ]. Studies have revealed alterations in miRNA levels in arterial hypertension, dyslipidemia, atherosclerosis, and inflammation [ 111 , 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, HDAC inhibitors and DMNT inhibitors are not selective for brain regions and cell types ( Xu et al, 2020b ). Non-specific HDAC inhibitors may cause a variety of adverse reactions, including weight loss, dysgeusia, electrolyte changes, and arrhythmia ( Kao and Lin, 2019 ). So, it is more appropriate to choose epigenetic drugs that target specific epigenetic modifications rather than affect global modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from activation of transcription factors, histone modification is also common in stroke and also plays an important part in controlling GLUT1 gene transcription (Kao & Lin, 2019 ). Inhibition of histone deacetylase (HDAC) leads to significant GLUT1 acetylation and increases GLUT1 expression (Chen et al., 2015 ).…”
Section: Regulation Of Ec‐glut1 After Strokementioning
confidence: 99%